For byte-oriented stream cipher on based with a uniform density the nonlinear substitutions algorithm - Белецкий, Анатолий Яковлевич; Навроцкий, Денис Александрович; Семенюк, Александр Иванович (Ukrainian Information Security Research Journal, 2016)
This article discusses the construction of a new byte-ori-ented synchronous stream encryption algorithm, which encrypts the gamma-stochastic sequence of bitsformed by a set of primitives uniformly dense nonlinear substitution S−blocks). Evenly dense are those entities nonlinear sub-stitution reactions which are evenly distributed on the sur-face of the scattering diagram of the primitive. A variant of the synthesis of uniformly dense S−boxes, which scat-terplot exceed the quality characteristics of the respective scatterplot indicators nonlinear substitution algorithm Rijndael block. A comparative analysis of the effectiveness of cryptographic transformations developed and most popular stream encryption algorithms. The directions of application of the proposed codes in various applications.